Stakeholder in conservation projects in Malaysia / Nur Fatin Nabilah Salehuddin - Salehuddin, Nur Fatin Nabilah (Faculty of Architecture, Planning and Surveying, 2013)
Conservation activities basically involve certain professionals, organizations, bodies, contractors and consultants and etc (stakeholder). Before practising building conservation, one including an architect, building contractor, planner or anyone who has the interest in saving an historic building must have a broad understanding of the field itself. This is of course to ensure that any action carried out during the conservation work is properly performed and is in accord not only with the building requirements but is within the scope of contemporary knowledge of the subject. (Dr. A. Ghafar Ahmad, 1994) In this research, it will generally focus on the investigation on identifying the true stakeholder in conservation projects. Basically, the research will be mainly reviewing the requirement and criteria that a true stakeholder should encompassed. In order to find the true stakeholder, investigation will be done through the processes which are elaborated in this research. In order to achieve the goals of the academic research, three (3) objectives are outlined as follow. To identify the stakeholders involved in conservation projects. To investigate the requirements and criteria should be encompass by the stakeholder in order to be appointed in conservation projects.To evaluate the significance of appointing only true stakeholder in conservation projects. Overall, the findings show that the stakeholders in conservation projects are involved contractors, conservator, workmen/craftsmen, local authority and etc. it is also proven that all this listed professional or workers are encompassed the criteria and requirements which needed within in themselves.